Patterns of phosphorylated tau accumulation in a spectrum of acquired and developmental brain lesions associated with refractory epilepsy - Mrzyglod, Alicja; Mebrouk, Anya; Bartkiewicz, Joanna; El Hachami, Hanaa; Ryniejska, Maritchka; de Tisi, Jane; Coras, Roland; Blumcke, Ingmar; Xiao, Fenglai; Miserocchi, Anna; McEvoy, Andrew; Koepp, Matthias; et al. (Epilepsia, 2025)
Objective: Phosphorylated tau (pTau) has been reported in surgical resections in refractory epilepsy. It is unclear whether this is activity-driven physiological pTau or signifies the advent of neurodegenerative cascades, relevant to memory decline. To date, primarily hippocampal sclerosis and focal cortical dysplasia (FCD) type II have been studied. We aimed to explore pTau in a range of acquired and developmental epileptogenic pathologies to assess its prevalence and identify potential drivers. Method: A total of 104 cases were studied representing FCD IA (n = 11), FCD IIIA (n = 5), FCD IIIB (n = 6), cavernoma (n = 11), Sturge–Weber leptomeningeal angiomatosis (n = 10), meningioangiomatosis (n = 4), perinatal infarcts (n = 9), Rasmussen encephalitis (RE; n = 6), gray matter heterotopia (n = 6), old scars (n = 10), and temporal lobe encephaloceles (n = 7); we also included focal microinjuries following prior stereoelectroencephalography at different ages (n = 19; four in lesion-negative cases). pTau was evaluated with AT8 immunohistochemistry, with further multiplex panels of AT8 with other established pTau markers (AT100, AT180, PHF1, CP13), pS6, glial fibrillary acidic protein, reelin, calbindin, and Tbr1 in selected cases. Labeling in the lesion was compared with adjacent cortex and clinical factors such as epilepsy duration. Results: pTau was identified in low to moderate levels in 60% overall, mainly localized to the epileptogenic lesion and more frequent in vascular malformations (74%–100%). pTau was noted in the superficial cortex across pathologies including encephaloceles, associated with superficial gliosis. In perinatal infarcts, distinct pTau patterns were noted in the superficial ulegyric cortex and heterotopic neuronal islands. Glial pTau was rare, and FCD IA, FCD IIIA/B, and microinjuries were negative. Variable regional expression of AT8 and mTOR activation markers (pS6) was noted, including in one RE case. Higher pTau expression was associated with older age at surgery and at onset of epilepsy, suggesting additional age-related vulnerability. Significance: Our findings highlight localized and distinct patterns of pTau in some epilepsy pathologies. Plausible pathomechanisms include local vascular insufficiency, neuronal dysmaturation, and aging as well as seizure activity and provide direction for future exploration.
CRIS-Team Scopus Importer:2025-05-16
Keywords: acquired scar; developmental; focal epilepsy; tau